Rural Youth Entrepreneurial Aspiration: An Assessment of TPB and Self-Efficacy - Abdul Rahman, Nor Irwani; Mursidi, Amalina; Suffarruddin, Suhaida Herni; Rusdi, Nur Rasyidah Aida Hazwani (UUM Press, 2024)
This study examines the factors influencing entrepreneurial intention among rural youth in Malaysia, focusing on the roles of attitude, perceived behavioural control, subjective norms, and self-efficacy within the Theory of Planned Behavior (TPB). Hence, TPB framework is proposed to be applied into rural contexts, it explores how self-efficacy interacts with psychological and social factors to shape entrepreneurial aspirations This study employed a quantitative approach, where valid data from 346 respondents were collected through an electronic survey over eight weeks. The subsequent analysis conducted with SPSS 24 and SmartPLS 4.0, tested ten proposed hypotheses. The findings reveal significant positive correlations between all three attitudinal factors (attitude, subjective norms, and perceived behavioural control) and entrepreneurial intention, with self-efficacy identified as a key mediator. Despite potential reservations about entrepreneurship, rural youth with higher self-efficacy are more likely to pursue entrepreneurial activities, emphasizing the importance of self-belief in fostering entrepreneurial success. The study highlights managerial implications, advocating for targeted self-efficacy enhancement programs such as entrepreneurship training and mentorship, as well as policies that provide access to resources and support networks tailored to rural youth. However, a limitation of the study is the lack of exploration into strategies for building self-efficacy. Future research should explore innovative methods, such as virtual reality (VR) simulations, to further enhance self-efficacy and entrepreneurial intentions